2019
DOI: 10.18502/aoh.v3i1.346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Workload and Human Errors in Nurses

Abstract: Background: Identification of human errors and their related factors in nurses dealing with the health of humans is important. Considering that much workload can increase the risk of human error, this study aimed to investigate the relationship between workload and human errors among nurses working in educational hospitals of Kerman University of Medical Sciences. Methods: This descriptive-analytical study was performed on 145 nurses from educational hospitals affiliated to Kerman University of Medical Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mental demand, physical demand, temporary demand, effort, performance and frustration level are important dimensions on workload [6]. Increasing the mental workload among health workers in this condition is very important; some studies have shown that the increased mental workload of these employees can lead to medical errors and put co-workers, patients, and his or her family at risk [7,8]. The increased mental workload can also cause burnout, dissatisfaction, stress, and reducing the patient's safety and health [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mental demand, physical demand, temporary demand, effort, performance and frustration level are important dimensions on workload [6]. Increasing the mental workload among health workers in this condition is very important; some studies have shown that the increased mental workload of these employees can lead to medical errors and put co-workers, patients, and his or her family at risk [7,8]. The increased mental workload can also cause burnout, dissatisfaction, stress, and reducing the patient's safety and health [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, both nurses and doctors acknowledged the system’s impact on reducing workload and human error [ 25 ]. Reduction in workload is not merely a procedural benefit, but it can also enhance job satisfaction and reduce burnout among healthcare staff.…”
Section: Discussionmentioning
confidence: 99%